Transient trade and the distribution of infrastructural knowledge: Bolivians in China. Issue 1 (1st March 2019) - Müller, Juliane
This article deals with transient migration of Bolivian traders and grassroots entrepreneurs to China. I trace prior experiences of traders with Asian and Chinese agents in South America to understand current transregional connections, and persistent trading practices and rationales. A growing conviction among Bolivians to travel to China and buy first-hand from factories in Guangzhou, Shenzhen, Yiwu and Shanghai on the one hand, and a cautious handling of information and contacts among them on the other, have stimulated the emergence of commercial intermediaries. Very few of the Bolivian brokers, however, have settled down in China. The trade has remained highly transient with about 6, 000 Bolivian traders and agents commuting each year back and forth to China. I explore the sources and effects of this transient trade, in particular the distribution of knowledge about infrastructure, technical and legal procedures to spur the inter-continental flow of goods.